Explanation:
Given
![y=x^2-2x-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/huq06ct8g227fzowg0gj4oy4obzdaa49mp.png)
Putting x = -2 in the function
![y=x^2-2x-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/huq06ct8g227fzowg0gj4oy4obzdaa49mp.png)
![y=\left(-2\right)^2-2\left(-2\right)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/g5m0of54fi0ule6l7lcpuoqk72pt6dukim.png)
= 4 + 4 - 3
= 5
(x, y) = (-2, 5)
Putting x = -1 in the function
![y=x^2-2x-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/huq06ct8g227fzowg0gj4oy4obzdaa49mp.png)
![y=\left(-1\right)^2-2\left(-1\right)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/u7o3irq8hbefxcwimjclze9omdcqz4vw69.png)
= 1 + 2 - 3
= 0
(x, y) = (-1, 0)
Putting x = 0 in the function
![y=\left(0\right)^2-2\left(0\right)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lgkyvknq8zki7c9ytkrskomwnpf47zxvso.png)
= 0 - 0 -3
= -3
(x, y) = (0, -3)
Putting x = 1 in the function
![y=\left(1\right)^2-2\left(1\right)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ps7by7xxpyvosjaoif3rnusizlqe2ut3bk.png)
= 1 - 2 - 3
= -4
(x, y) = (1, -4)
Putting x = 2 in the function
![y=\left(2\right)^2-2\left(2\right)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/yieyzpj1boq1cflhh1yazjji232fut0twt.png)
= 4 - 4 - 3
= -3
(x, y) = (2, -3)
Putting x = 3 in the function
![y=\left(3\right)^2-2\left(3\right)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5dt88qqkan88ufu85bilzif30cmzseyils.png)
= 9 - 6 - 3
= 0
(x, y) = (3, 0)
Putting x = 4 in the function
![y=\left(4\right)^2-2\left(4\right)-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1nsx3sb8maiylow1rv543nnxhjnehkckao.png)
= 16 - 8 - 3
= 5
(x, y) = (4, 5)
Therefore, completing the table:
x y
-2 5
-1 0
0 -3
2 -4
3 0
4 5